(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe clinical characteristics, labor time, some factors related to labor time and comment on the effect of labor time on women giving birth at normal and full term at the Department of Obstetrics and Gynecology of General Hospital Nghe An in 2022. Research Methods: Analytical cross-sectional descriptive study Results: A study of 295 women at the Department of Obstetrics and Gynecology, Nghe An Hospital, to investigate the clinical characteristics of the labor process and some factors related to the labor time of pregnant women. Information was collected by examination according to a pre-designed medical record form. Results: Mean BMI was 25.47 ± 2.31. The most common first sign of labor is abdominal pain 44.1%; pink mucus or vaginal bleeding 33.5%. The average labor time of pregnant women with a baby is 19.32 ± 12.19 hours; of pregnant women at 11.90 ± 7.90 hours. The rate of urinary retention was 13.5%; the rate of postpartum hemorrhage is 2.4%; the indication rate for artificial amniotomy was 73.2%. There is a weak positive correlation (r = 0.284, p<0.001, R2 = 8.1%) between maternal BMI and the duration of stage 1a labor; The group of women with BMI > 30 had the longest stage 1a labor (p < 0.05). Conclusion: Prolonged labor is an increased length of labor compared with women with the same risk factors. Labor for a long time can lead to serious complications or sequelae if not detected early and treated promptly. Complications may be: fetal distress in labor, threatened uterine rupture, uterine rupture, genitourinary fistula formation of the bladder or rectum, neonatal sepsis, postpartum infection. Therefore, monitoring the labor process and detecting possible problems will limit the changes that affect the health of the mother during labor